2014
DOI: 10.7860/jcdr/2014/8966.4202
|View full text |Cite
|
Sign up to set email alerts
|

Correlation Between Haemoglobin Level and Electrocardiographic (ECG) Findings in Anaemia: A Cross-Sectional Study

Abstract: Background: Anaemia affects the body by decreased oxygen (O 2 ) carrying capacity of the blood. There is growing evidence that anaemia contributes to cardiac disease and death. It causes O 2 supply -demand myocardial mismatch causing myocardial ischemia. There is diversity of opinion available in literature on reports of electrocardiographic (ECG) changes in anaemia. Aim:To study the ECG changes in anemic population and to correlate ECG changes seen with increasing severity of anaemia. Materials and Methods:In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 18 publications
1
3
0
Order By: Relevance
“…As shown by Shakuntala et al [ 21 ] we also observed that in the group which had acute blood loss, there was a strong correlation between change in hemoglobin and ST segment with a Pearson coefficient of 0.608 ( P -value = 0.012). ST segment depression reflects myocardial ischemia and as the myocardium has a higher extraction ratio of oxygen than the other tissues, changes in the ST segment are also reflective of hemoglobin content and may be a sensitive indicator of acute hypovolemic anemia.…”
Section: Discussionsupporting
confidence: 80%
“…As shown by Shakuntala et al [ 21 ] we also observed that in the group which had acute blood loss, there was a strong correlation between change in hemoglobin and ST segment with a Pearson coefficient of 0.608 ( P -value = 0.012). ST segment depression reflects myocardial ischemia and as the myocardium has a higher extraction ratio of oxygen than the other tissues, changes in the ST segment are also reflective of hemoglobin content and may be a sensitive indicator of acute hypovolemic anemia.…”
Section: Discussionsupporting
confidence: 80%
“…Thus, this decrease in amplitude of QRS and T waves has been reported during anemia. 43 The observed changes in ECG could be linked to hypoxia-induced changes in ATPdependent channels. During cardiac ischemia, ATP levels drop and then K ATP channels are opened to reduce ADP and to prevent excessive depolarization, 44 shortening the action potential duration, maintaining excitability, and protecting the metabolism of myocytes from the injuries caused by ischemia.…”
Section: Discussionmentioning
confidence: 99%
“…[6][7][8] In several previous studies, anaemia was shown to change the morphology of the electrocardiogram (ECG), and researchers suggested that mismatching oxygen demand and supply in the myocardium affects the ECG. [9][10][11][12] However, it is not easy to detect such subtle ECG changes, so the current state of the ECG is not useful for detecting anaemia. Screening for anaemia with an ECG would be straightforward, and patients who were suspected to be anaemic could be referred for confirmatory laboratory tests.…”
Section: Introductionmentioning
confidence: 99%